Sustainable Consumption Patterns Adopting BIM-Enabled Energy Optimization-A Case Study of Developing Urban Centre - Hasan, I. (HARD Publishing Company, 2022)
Population and urbanization have resulted in increased demands of high-rise buildings to meet the spatial challenge. However, energy consumption by high risers have become a serious concern, especially in developing countries. Supporting the 2030 agenda for sustainable development needs improvement in energy efficiency at global as well as local levels, thus requiring proper sustainable consumption patterns. The current work explores an innovative approach to optimize the operational energy consumption utilizing building orientation at the design stage. A 3D parametric BIM model of a sixteen-story high-rise building was analysed for the proposed location. A rotation scheme with an angular increment of 45Â° was devised to observe the energy consumption patterns. The energy analysis and Building Energy Quotient (bEQ) level observed energy-intensive pattern at the proposed orientation. For the rotation scheme analysed, almost 70 achieved a âPoorâ rating of bEQ, whereas the remaining were at âFairâ level. Rotating the buildingâs face in the West â North or East â South direction, annual energy consumption pattern observed a decreasing trend and vice versa. Rotation 02 (45Â°) resulted a minimum annual energy consumption was further optimized opting certain design parameters, thus resulting in an overall annual energy saving of almost 64. This improved rating scale from a Fair to âVery Goodâ status, also meeting the challenge of Architecture 2030. The study observed proper orientation-based energy analysis of the built environment at the design stage offers promising prospects for optimized consumption patterns for sustainable developments. Â© 2022, HARD Publishing Company. All rights reserved.